2002
DOI: 10.4269/ajtmh.2002.67.586
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine responses during acute simian Plasmodium cynomolgi and Plasmodium knowlesi infections.

Abstract: Abstract. Experimental infection of non-human primates with simian malaria parasites offers a controlled system to study malarial immunity. Plasmodium cynomolgi (P. vivax-like) and P. knowlesi (P. falciparum-like) infections in the rhesus monkey were used as a model to test the hypothesis that initial acute infection stimulates type 1/pro-inflammatory cytokine expression followed by a gradual type 2/anti-inflammatory response upon re-infection. This study analyzed cytokine gene expression (interleukin-12, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 21 publications
1
16
0
1
Order By: Relevance
“…It is not understood what is causing the death of heavily infected mosquitoes. One possibility is that there is something toxic in the blood of monkeys that have high levels of P. knowlesi infection, such as a cytokine [42], which might be detrimental to mosquitoes. However, if a toxic substance was ingested, mosquito mortality might be expected to be highest soon after they fed on an infected monkey.…”
Section: Discussionmentioning
confidence: 99%
“…It is not understood what is causing the death of heavily infected mosquitoes. One possibility is that there is something toxic in the blood of monkeys that have high levels of P. knowlesi infection, such as a cytokine [42], which might be detrimental to mosquitoes. However, if a toxic substance was ingested, mosquito mortality might be expected to be highest soon after they fed on an infected monkey.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with other previous studies where malaria-related anaemia is more severe in children rather than in adults [79,80] due to increased demand of iron by the body as growth is rapid in children. In 2002, Praba-Egge and her colleagues [81] carried out experimental infection of non-human primates with P. knowlesi and Plasmodium cynomolgi . The study reported that anaemia was observed in P. knowlesi- infected monkeys after primary and/or repeated infection.…”
Section: Discussionmentioning
confidence: 99%
“…, see [20; 36; 74; 81; 82; 83; 84; 85; 86; 87; 88]). Because the parasite is threatened by the immune system, it has evolved escape strategies, including the intriguing use of antigenic variation mechanisms [89; 90; 91].…”
Section: Malaria As the Paradigm Infectious Diseasementioning
confidence: 99%